2017
DOI: 10.3791/55771
|View full text |Cite
|
Sign up to set email alerts
|

Intracortical Inhibition Within the Primary Motor Cortex Can Be Modulated by Changing the Focus of Attention

Abstract: It is well recognized that an external focus (EF) compared with an internal focus (IF) of attention improves motor learning and performance. Studies have indicated benefits in accuracy, balance, force production, jumping performance, movement speed, oxygen consumption, and fatiguing task. Although behavioral outcomes of using an EF strategy are well explored, the underlying neural mechanisms remain unknown. A recent TMS study compared the activity of the primary motor cortex (M1) between an EF and an IF. More … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
14
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 13 publications
(16 citation statements)
references
References 53 publications
2
14
0
Order By: Relevance
“…In line with this proposal, it has been shown that isometric contractions can be maintained longer when an external focus of attention is adopted (Kuhn et al, 2017a). Interestingly, this improvement of performance was accompanied by an increase in SICI (Kuhn et al, 2017a; Kuhn et al, 2017b) and an increase in surround inhibition (Kuhn et al, 2018).…”
Section: Discussionmentioning
confidence: 98%
“…In line with this proposal, it has been shown that isometric contractions can be maintained longer when an external focus of attention is adopted (Kuhn et al, 2017a). Interestingly, this improvement of performance was accompanied by an increase in SICI (Kuhn et al, 2017a; Kuhn et al, 2017b) and an increase in surround inhibition (Kuhn et al, 2018).…”
Section: Discussionmentioning
confidence: 98%
“…Motor inhibition is essential for quality of motor execution and particularly for modulating motor cortex output during fine movements, and the increased prominence of SICI in female PD patients may reflect better preserved capacity for movement control at level of the motor cortex. It has been suggested that decreased SICI in PD reflects mainly decreased threshold of excitatory neurons mediating short‐interval intracortical facilitation, with only a minor contribution of impaired synaptic inhibition .…”
Section: Discussionmentioning
confidence: 99%
“…For example, in a study with elaborated TMS protocols (paired-pulse and subthreshold stimulation paradigms), Kuhn and co-workers 27 demonstrated that adopting an EF contrasted to an IF enhances cortical inhibition within M1. The enhanced activity of inhibitory interneurons within M1 may indicate a reduced motor-cortical activation 11 , 27 , 28 , which could be interpreted as a more efficient and more automatic mode of motor control when adopting an EF contrasted with an IF.These data might therefore be considered as a more efficient neural strategy. Besides the effects found in the prime-mover, there is also evidence that adjacent muscles are activated differently when participants use an EF versus an IF.…”
Section: Introductionmentioning
confidence: 99%
“…For example, Chow and colleagues 24 demonstrated that the decreased balance performance (bigger sway path) when using an IF over an EF in young adults was accompanied by a higher T3 (verbal-analytical) and Fz (motor-planning) coherence which reflects increased verbal-analytical involvement during motor planning and control 25 , 26 . Moreover, using different TMS protocols, recent studies 11 , 27 , 28 demonstrated altered neural activation in M1 for the muscle directly involved in the motor task (prime mover) but also the surrounding and/or antagonistic muscles. For example, in a study with elaborated TMS protocols (paired-pulse and subthreshold stimulation paradigms), Kuhn and co-workers 27 demonstrated that adopting an EF contrasted to an IF enhances cortical inhibition within M1.…”
Section: Introductionmentioning
confidence: 99%